Characteristics of intradialytic hypotension: Experience of agadir center-morocco - Akhmouch I; Bahadi A; Zajjari Y; Bouzerda A; Asserraji M; Alayoud A; Montasser D; Moujoud O; Aattif T; Kadiri M; Zemraoui N; Elkabbaj D; et al. (Saudi Journal of Kidney Diseases and Transplantation, 2010)
We report in this retrospective study the experience of our hemodialysis (HD) center in the incidence of intradialytic hypotension (IDH) over 18 months. We first studied the de-mographic, clinical, biological and morphological data of our 52 HD patients and compared the characteristics of patients with frequent IDH and those without. We found that factors signi-ficantly associated with IDH include diabetes, left ventricular hypertrophy, impaired diastolic function, weight gain and high ultrafiltration rates. Despite these results, further larger studies are required to confirm them.